Pengaruh Pertumbuhan Aset, Profitabilitas, dan Dividend Payout Ratio (DPR) terhadap Nilai Perusahaan dengan Struktur Modal Sebagai Variabel Intervening pada Sub Sektor Properti - Anggraini, Ria Sofia (Universitas Proklamasi 45, 2025)
This research aims to determine the effect of asset growth, profitability, and dividend payout ratio (DPR) on company value, with capital structure as an intervening variable, in the property sub-sector listed on the BEI from 2018 to 2022. Only 6 out of 80 property companies passed the selection for this research. The method used is a descriptive quantitative approach with data analysis conducted using EViews. The results show that asset growth does not affect company value. Profitability and DPR have a positive impact on investor perceptions of a company's value, resulting in an increase in that value. Capital structure does not mediate the relationship between these factors. These results are useful for investors and entrepreneurs in company management.